Predictors of red blood cell transfusion after cardiac surgery: a prospective cohort study - Lopes, Camila Takao; Brunori, Evelise Helena Fadini Reis; Cavalcante, Agueda Maria Ruiz Zimmer; Moorhead, Sue Ann; Lopes, Juliana de Lima; Barros, Alba Lucia Bottura Leite de (Revista da Escola de Enfermagem da USP, 2015)
OBJECTIVE To identify predictors of red blood cell transfusion (RBCT) after cardiac surgery. METHOD A prospective cohort study performed with 323 adults after cardiac surgery, from April to December of 2013. A data collection instrument was constructed by the researchers containing factors associated with excessive bleeding after cardiac surgery, as found in the literature, for investigation in the immediate postoperative period. The relationship between risk factors and the outcome was assessed by univariate analysis and logistic regression. RESULTS The factors associated with RBCT in the immediate postoperative period included lower height and weight, decreased platelet count, lower hemoglobin level, higher prevalence of platelet count